Comprehensive Review of Advanced Biomaterials in Dentistry and Their Role in Redefining Aesthetic and Functional Restoration - Salloum, Rand Sulaiman Bin; Alqutub, Samiah Maher; Alharthi, Ghadah Ayedh; Madkhali, Atheer Mohammed; Althagafi, Athir Ibrahim; Almosallam, Amal Ali; Banjar, Ameena Talal; Dwead, Roaa Mohammed Ali; Almotairi, Bushra Mohammed; Alhashim, Duaa Mohammed (Journal of Ecohumanism, 2024)
Restorative dentistry has experienced developments in biomaterials, especially in cosmetics and mechanics. The need for procedures that would restore and function and provide an esthetic appearance has led to the development of sophisticated biomaterials. These materials contribute to the solution of traditional problems associated with durability, biocompatibility issues, and the integration of the prosthesis with natural teeth. This review describes the different forms of advanced biomaterials used in dental vital processes, including ceramics, composites, and bioactive materials. This paper details these materials' properties, uses, advantages, and limitations to provide a holistic understanding of the materials and their function in reshaping the basis of aesthetics and functionality in dentistry. It also discusses the part played by post-industrial technologies like CAD/CAM, 3D printers, and nanotechnologies in improving the performance of dental biomaterials. Lastly, the review demonstrates the detailed potential of dental biomaterials toward the future of restorative dentistry.